Efficacy of Constitutional Homoeopathic Medicine in Obesity (Advancements in Homeopathic Research, 2022)
This clinical trial was carried out to ascertain the effects of different homoeopathic medicines in cases of obesity. In this study 30 cases were considered. The 30 cases were divided into 2 groups: (15 patients, selected randomly in each group) ● Group I (Experimental) – Homoeopathic treatment + Lifestyle modification. ● Group II (Control) – Placebo + Lifestyle modification. Clinical cases with B.M.I between 25 & 39.9 were included in this clinical trial of over one year. It was seen that middle age group patients are more affected by obesity due to their dietary habits & lifestyle. It was also seen through the study that certain homoeopathic medicines were proved beneficial in cases of obesity. It was also seen through the study that within few months, most of the patients were treated successfully & hence there is a vast scope of homoeopathic medicines in obesity.The overall result of each group is as follows – ● Group I – The number of patients showing improvement is 09 (60%), Status Quo is 5 (33%) & number of patient worse is 1 (07%). ● Group II – The number of patients showing improvement is 4 (27%), Status Quo is 11 (73%) & number of patients worse is 0 (00%). This shows that the homoeopathic medicines were effective in cases of obesity in, where patients were regular in their treatment and followed proper diet and regimen, whereas placebo was not as effective. This verifies the efficacy of homoeopathy in reducing body mass index. Certain symptoms of some homoeopathic medicines were also clinically verified.
Keywords: homoeopathic; patients; clinically; symptoms